Actual performance of mechanical ventilators in ICU: a multicentric quality control study - Govoni L; Dellaca' RL; Peñuelas O; Bellani G; Artigas A; Ferrer M; Navajas D; Pedotti A; Farré R (Medical Devices: Evidence and Research, 2012)
Leonardo Govoni,1 Raffaele L Dellaca,1 Oscar Peñuelas,2,3 Giacomo Bellani,4,5 Antonio Artigas,3,6 Miquel Ferrer,3,7 Daniel Navajas,3,8,9 Antonio Pedotti,1 Ramon Farré3,81TBM-Lab, Dipartimento di Bioingegneria, Politecnico di Milano University, Milano, Italy; 2Hospital Universitario de Getafe – CIBERES, Madrid, Spain; 3CIBER de Enfermedades Respiratorias, Bunyola, Spain; 4Department of Experimental Medicine, University of Milan, Bicocca, Italy; 5Department of Perioperative Medicine and Intensive Care, San Gerardo Hospital, Monza (MI), Italy; 6Critical Care Center, Sabadell Hospital, Corporació Sanitaria Universitaria Parc Tauli, Universitat Autonoma de Barcelona, CIBERES, Spain; 7Department of Pneumology, Hospital Clinic, IDIBAPS, Barcelona, Spain; 8Unitat de Biofísica i Bioenginyeria, Facultat de Medicina, Universidad de Barcelona-IDIBAPS, Barcelona, Spain; 9Institut de Bioenginyeria de Catalunya, Barcelona, SpainAbstract: Even if the performance of a given ventilator has been evaluated in the laboratory under very well controlled conditions, inappropriate maintenance and lack of long-term stability and accuracy of the ventilator sensors may lead to ventilation errors in actual clinical practice. The aim of this study was to evaluate the actual performances of ventilators during clinical routines. A resistance (7.69 cmH2O/L/s) – elastance (100 mL/cmH2O) test lung equipped with pressure, flow, and oxygen concentration sensors was connected to the Y-piece of all the mechanical ventilators available for patients in four intensive care units (ICUs; n = 66). Ventilators were set to volume-controlled ventilation with tidal volume = 600 mL, respiratory rate = 20 breaths/minute, positive end-expiratory pressure (PEEP) = 8 cmH2O, and oxygen fraction = 0.5. The signals from the sensors were recorded to compute the ventilation parameters. The average ± standard deviation and range (min–max) of the ventilatory parameters were the following: inspired tidal volume = 607 ± 36 (530–723) mL, expired tidal volume = 608 ± 36 (530–728) mL, peak pressure = 20.8 ± 2.3 (17.2–25.9) cmH2O, respiratory rate = 20.09 ± 0.35 (19.5–21.6) breaths/minute, PEEP = 8.43 ± 0.57 (7.26–10.8) cmH2O, oxygen fraction = 0.49 ± 0.014 (0.41–0.53). The more error-prone parameters were the ones related to the measure of flow. In several cases, the actual delivered mechanical ventilation was considerably different from the set one, suggesting the need for improving quality control procedures for these machines.Keywords: equipment and supplies, medical devices, intravenous, quality assurance, health care quality assessment, ventilator accuracy, ventilation error